Pengaruh Brand Image dan Aksesibilitas Digital Banking terhadap Loyalitas Nasabah Bank BSI KCP Bojonegoro-Sumberrejo - Novia Rohmatullaili (Alkasb: Journal of Islamic Economics, 2023)
Technological developments in the 5.0 era are now growing, with the development of Islamic bank technology focused on developing and continuously innovating BSI mobile by continuing to add features needed by the community. In addition, the brand is also important for the continuity of the development of the bank, because there are still very few banks that use the Sharia brand in their institutions. From the results of the test carried out the validity test is said to be valid because the results of Rcount is greater than Rtable (0.197), the results of the reliability test of X1, X2 and Y are said to be reliable because they have fulfilled statistical requirements, the results of the multicollinearity test get a result of 2.912 which is greater than 5 it can be said to have a multicollinearity relationship. the results of the heteroscedasticity test are 0.000 <0.05 which means there are symptoms of heteroscedasticity, the normality test, in the histogram the line is facing down normally, the dot plots are close to the line which indicates normal, table one the Kolmogorof Smirnov sample is 0.075 <0.134 the data is normally distributed. and also supported by the results of the Asymp Sig (2-Tailed) value of 0.627> 0.05, the data is normally distributed. partial test (T) 5.776> 1.661 (information H0 is rejected), simultaneous test (F) 148.627> 3.090 then H0 is rejected. It can be said that Brand Image and digital banking accessibility have an effect of 75% on customer loyalty.